Sacred Jerusalem in the Arabic Textbooks of Basic School in Jordan an Analytical Study - Mohammad Al-Hawamdeh (My University, 2010)
This study aimed at proposing a list of the constituents of Sacred Jerusalem's image to be included in the Arabic textbooks of the basic school in Jordan. The study aimed as well at exploring the extent to which such constituents existed, be in sequence and had an integrative nature in the subject Arabic textbooks. In order to have these objectives attained, a made-valid instrument was prepared for analyzing the image of Sacred Jerusalem following the 'construction model of analysis'. The 'descriptive model of analysis' was also used for analyzing the Arabic textbooks of Jordan's basic school. Pertaining to findings, first of all, five constituents were proposed, having 35 dimensions of Sacred Jerusalem's image in total, distributed as follows: (i) the history of Jerusalem with 7 dimensions, (ii) the geography of Jerusalem with 2 dimensions, (iii) Sacred Jerusalem and Zionism with 8 dimensions, (iv) the position of Jerusalem to Arabs and Muslims with 8 dimensions, and (v) the sacred, archeological milestones of Jerusalem with 10 dimensions. Secondly, the extent to which such constituents were included in the subject Arabic textbooks was seen of variance; some constituents came less included or were not included at all. Grades 1 and 2's Arabic textbooks did not include any of which to refer to Sacred Jerusalem's image. Finally, the level at which these constituents might be in sequence was seen low, and there were no statistically significant differences (α=0,05) pertaining to the level at which the constituents of Jerusalem's image in the Arabic textbooks of basic school in Jordan had an integrative nature.

هدفت الدِّراسة إلى اقتراح قائمة لمكونات صورة القُدْس الشَّريف التي ينبغي تضمينها في كتب اللُّغَة العَرَبيَّة في المَرحَلة الأسَاسيَّة في الأردن، والكشف عن درجة توافر مكونات صورة القُدْس الشَّريف، ومستوى تتابعها، وتكاملها في كتب اللُّغَة العَرَبيَّة. ولتحقيق أهداف الدِّراسة، قام الباحث بإعداد أداة لتحليل صورة القُدْس الشَّريف باتباع المنهج البنائي، وتم استخراج دلالات صدق الأداة وثباتها، كما استخدمت الدِّراسة المنهج الوصفي لتحليل كتب اللُّغَة العَرَبيَّة في المَرحَلة الأسَاسيَّة. وكشفت الدِّراسة عن النتائج الآتية: اقتراح خمسة مكونات تتضمن (35) بعداً لصورة القدس الشريف، موزعة على النحو الآتي: المكون الأول: تاريخ القدس الشريف، ويتضمن (7) أبعاد. والمكون الثاني: جغرافية القدس، ويتضمن بعدين. والمكون الثالث: القدس الشريف والحركة الصهيونية، ويتضمن (8) أبعاد. والمكون الرابع: مكانة القدس الشريف عند العرب والمسلمين، ويتضمن (8) أبعاد. والمكون الخامس: المعالم الأثرية والمقدسة في القدس الشريف، ويتضمن (10) أبعاد. كما تمَّ الكشف عن تفاوت نسبة تضمين مكونات صورة القُدْس الشَّريف في كتب اللُّغَة العَرَبيَّة في المَرحَلة الأسَاسيَّة، فبعض المكونات وأبعادها جاءت مضمنة بدرجة منخفضة أو لم تضمن أساسا. وبيّنت نتائج الدِّراسة خلو كتابي اللُّغَة العَرَبيَّة للصفين الأول والثاني الأساسيين من أية صورة للقدس الشريف. في حين كان مستوى تتابع مكونات صورة القُدْس الشَّريف المتضمنة في كتب اللُّغَة العَرَبيَّة منخفضاً. وأظهرت نتائج الدِّراسة عدم وجود فروق ذات دلالة إحصائية (α=0.05) في مستوى تكامل مكونات صورة القُدْس الشَّريف بين كتب اللُّغَة العَرَبيَّة في المَرحَلة الأسَاسيَّة كلّها.
القُدْسُ الشَّريفُ في كُتُبِ اللُّغَةِ العَرَبيَّةِ في المَرحَلةِ الأسَاسيَّةِ في الأُردنِّ "دراسة تحليليّة"